A study on analysis of malicious code behavior information for predicting security threats in new environments - Choi, Seul Ki; Lee, Taejin; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2019)
The emergence of new technologies and devices brings a new environment in the field of cyber security. It is not easy to predict possible security threats about new environment every time without special criteria. In other words, most malicious codes often reuse malicious code that has occurred in the past, such as bypassing detection from anti-virus or including additional functions. Therefore, we are predicting the security threats that can arise in a new environment based on the history of repeated malicious code. In this paper, we classify and define not only the internal information obtained from malicious code analysis but also the features that occur during infection and attack. We propose a method to predict and manage security threats in new environment by continuously managing and extending.
Keywords: Anti virus; Cyber security; Malicious codes; Malicious-code analysis; Security threats; Cyber security; Malicious code; Malware; Security threat